Gibalne navade prebivalcev področja Kaski v Nepalu v povezavi z zdravjem - Pečnik, Eva (Šport (Ljubljana), 2017)
The aim of the thesis was to determine correlations between physical habits and certain physical and mental aspects of health for adult Nepalese. For the field survey a personal questionary was designed with questions about socio-demographic data, health and physical habits. The sample consisted of 100 adult residents of Nepal from Kaski district with an average age of 28 years (SD = 7.2). The majority of them lived in the city of Pokhara. The obtained data were processed with the statistical program SPSS. To calculate the correlation of physical activities and exercise related with health problems and diseases as well as life satisfaction Spearman's correlation coefficient was used. Hypothesis testing was conducted at a 5 % level of risk. The result was that there was no correlation between the average time of physical activities and exercise within a week and the average number of health problems and diseases. Of statistical significance was the correlation between average time of exercise per week and an average rating of arguments about changes in a person's life, which was negative. The longer the time for exercise was, the less desire for changes in life was present.
Keywords: adult Nepalese; gibalne navade; health; Nepal; nutritional supplements; odrasli; physical habits; satisfactrion with life; sport; šport; zadovoljstvo z življenjem; zdravje